The Influence of Mental Health Education on the State of Dance Competition of College Students - Shuai Zhang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
In modern competitive sports, the optimal mental condition enables athletes to perform at the optimal competitive level. The competition is a test and confirmation of the talent level of the athletes. Performance in the competition is not only related to honor but also to the remuneration and future career of the athletes. This study administered a psychological test to twenty college dance athletes who participated in the 2022 National Undergraduate Dance Championships to ascertain the relationship between psychological training, psychological selection, and performance enhancement. In this investigation, a comparative before-and-after experimental design was used. Athletes were evaluated for mental state indicators two months before the competition to ascertain the baseline level of these indicators. Consequently, the emotional/physical depletion of international elite athletes was significantly higher than that of elite athletes, and their energy levels were significantly lower. In addition, psychological regulation has dramatically enhanced the level of psychological fatigue and mood state among athletes, as evidenced by the significant decrease in emotional/physical exhaustion among international athletes (P<0.01) and the significant decrease in panic among level 1 and 2 athletes (P<0.05). After regulation and control, the negative evaluation of sports and the dread factor have a highly significant correlation with sports performance and a highly effective predictive ability for sports performance.